Social life connects the world: Malaysian youth’s usage behaviour of social network sites - Wong, F.M.; Lean, M.L.; Fernandez, P.R. (2010)
The recent trend of using social network sites (SNS) is a globally widespread phenomenon. SNS such as Facebook, Friendster, MySpace and Twitter are popular among millions of users around the globe. SNS are used to build relationships, to communicate and share information, multimedia contents and daily happenings, and to increase their social networks for personal or business purposes. Thus, this study aims to investigate the main reasons for using SNS among Malaysian youth and their usage behaviour. In particular, this study also intends to look into their attitude towards SNS, and their overall usage experience. The investigation for this study is guided by the theoretical framework of Uses and Gratifications. Both quantitative and qualitative analyses, using survey and personal interview research, are employed to examine the uses and usage behaviours of SNS among Malaysian youth.